Back Cover: Proteomic analysis of human follicular fluid in poor ovarian responders during in vitro fertilization. Issue 6 (March 2017) - Oh, Jae Won; Kim, Seul Ki; Cho, Kyung‐Cho; Kim, Min‐Sik; Suh, Chang Suk; Lee, Jung Ryeol; Kim, Kwang Pyo
Abstract : DOI:10.1002/pmic.201600333 Poor ovarian response (POR) observed in controlled ovarian stimulation (COS) is often observed during in vitro fertilization and embryo transfer (IVF‐ET) cycles and is a major problem. It is difficult to predict POR, as there are no specific biomarkers known. In this study, we used quantitative proteomic analyses to investigate potential biomarkers that can predict poor response during IVF based on follicular fluid samples. Consequently, three proteins (PZP, RENI, and SRPX) were regarded as statistically significant. For more details, see the research article by Jae Won Oh et al., article number 1600333.